Controlled stepwise growth of siloxane chains using bivalent building units with different functionalities - Salingue, Nils; Lingenfelser, Dominic; Prunici, Pavel; Hess, Peter (Thin solid films, 2010)
Organic/inorganic hybrids of silicon and their subsequent chemical modification are of interest for tailoring and structuring surfaces on the nanoscale. The formation of organic (sub)monolayers on hydroxylated silicon surfaces was employed to synthesize molecular siloxane chains by stepwise wet-chemical condensation reactions. Functionalizations with small alkyl-monochlorosilanes, yielding dimethylsilyl, diisopropylsilyl, di-tert-butylsilyl terminations, and with an aryl-monochlorosilane, providing diphenylsilyl groups, were studied. The SiH moiety of these end groups could be selectively oxidized to the corresponding silanol. The reactivity of this group opened the possibility of bonding additional species step by step in bottom-up growth reactions. In particular, dimethylsiloxane units were studied as possible molecular building blocks. By repeating the oxidation and condensation reactions the stepwise growth of one-dimensional siloxane chains was demonstrated. The ongoing chain growth was characterized by attenuated total reflection Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, spectroscopic ellipsometry (NIR-UV), and contact-angle experiments.
Gesehen am 29.06.2023